Cholesterol metabolism promotes B‐cell positioning during immune pathogenesis of chronic obstructive pulmonary disease. Issue 5 (19th April 2018) - Jia, Jie; Conlon, Thomas M; Sarker, Rim SJ; Taşdemir, Demet; Smirnova, Natalia F; Srivastava, Barkha; Verleden, Stijn E; Güneş, Gizem; Wu, Xiao; Prehn, Cornelia; Gao, Jiaqi; Heinzelmann, Katharina; et al.
Abstract: The development of chronic obstructive pulmonary disease (COPD) pathogenesis remains unclear, but emerging evidence supports a crucial role for inducible bronchus‐associated lymphoid tissue (iBALT) in disease progression. Mechanisms underlying iBALT generation, particularly during chronic CS exposure, remain to be defined. Oxysterol metabolism of cholesterol is crucial to immune cell localization in secondary lymphoid tissue. Here, we demonstrate that oxysterols also critically regulate iBALT generation and the immune pathogenesis of COPD. In both COPD patients and cigarette smoke (CS)‐exposed mice, we identified significantly upregulated CH25H and CYP7B1 expression in airway epithelial cells, regulating CS‐induced B‐cell migration and iBALT formation. Mice deficient in CH25H or the oxysterol receptor EBI2 exhibited decreased iBALT and subsequent CS‐induced emphysema. Further, inhibition of the oxysterol pathway using clotrimazole resolved iBALT formation and attenuated CS‐induced emphysema in vivo therapeutically. Collectively, our studies are the first to mechanistically interrogate oxysterol‐dependent iBALT formation in the pathogenesis of COPD, and identify a novel therapeutic target for the treatment of COPD and potentially other diseases driven by the generation of tertiary lymphoid organs. Synopsis: COPD is the third leading cause of death worldwide with limited therapy. iBALT is a crucial contributor to COPD pathogenesis. Local airway production of oxysterols is crucial for iBALT formation without affecting B and T cell activation, whose inhibition offers new therapeutic potential. Oxysterol metabolizing enzymes CH25H and CYP7B1 are upregulated in airway epithelial cells of COPD patients and cigarette smoke‐exposed mice. Mice deficient in CH25H or the oxysterol receptor EBI2 failed to generate iBALT in their lungs and critically were protected against emphysema development following chronic cigarette smoke exposure. B cells failed to migrate ex vivo towards CS‐stimulated airways from Ch25h −/− mice or mice in which oxysterol synthesis genetically and pharmacologically had been blocked. Therapeutically, the CYP7B1 inhibitor clotrimazole resolved iBALT formation and attenuated cigarette smoke‐induced COPD in a murine model suggesting a novel therapeutic option for COPD patients. Abstract : COPD is the third leading cause of death worldwide with limited therapy. iBALT is a crucial contributor to COPD pathogenesis. Local airway production of oxysterols is crucial for iBALT formation without affecting B and T cell activation, whose inhibition offers new therapeutic potential.